An improved hydrocarbon generating model of source rocks and its application: a case study of shale oil in-situ transformation of the Yanchang Formation in the Ordos Basin. (1st February 2021) - Guo, Qiulin; Chen, Xiaoming; Wang, Jian; Chen, Ningsheng; Wu, Xiaozhi
Abstract: Hydrogen index, HI, and original hydrogen index, HIo, are important indicators for measuring the hydrocarbon generation potential of the source rock. Through addressing the shortcomings of existent HIo models, improved models are proposed to improve the coincidence between calculated and measured results. According to the statistics of rock pyrolysis and TOC data of 1, 249 cores taken in seven basins, key parameters of HIo models for types I, IIa, IIb, and III kerogen are obtained, complements quantitative evaluation methods for effective source rocks and provides a theoretical basis for evaluating in situ transformation of shale oil and hydrocarbon generating potential of deep source rocks. These models have been applied to evaluate the in situ transformed shale oil in the Yanchang Formation of the Ordos Basin, and the result reveals: (1) the transformed shale oil amounts to 375.9 × 10 8 t, and natural gas to 4.17 × 10 12 m 3 ; the average resource abundance of shale oil is 114.6 × 10 4 t/km 2 ; the new organic porosity originated averages 6.9%; and the sweet spot zones of shale oil are mainly distributed on the north of Zhengning and Well Mu78; (2) in situ transformation would increase in situ resources, gas-to-oil ratio, porosity and permeability, and improve the productivity of shale oil in the Chang 7 member.